Implementasi Pendekatan Pembelajaran Mendalam dalam Meningkatkan Keterampilan Berpikir Kritis Siswa Sekolah Dasar - I Gede Panca; Chairan Zibar L. Parisu (Journal of Humanities, Social Sciences, and Education, 2025)
Deep learning is a pedagogical approach that emphasizes active student involvement in meaningfully understanding concepts, rather than simply memorizing information. At the elementary school level, this approach is highly relevant because it can foster critical thinking skills from an early age. This article is a literature review that aims to analyze the implementation of the deep learning approach in improving elementary school students' critical thinking skills. Previous research shows that deep learning can encourage students to explore, reflect, analyze, and synthesize knowledge. By integrating strategies such as problem-based learning, project-based learning, and inquiry-based learning, students not only understand the material conceptually but also develop the ability to ask critical questions, evaluate information, and connect knowledge to real-life situations. Furthermore, the use of digital technology and interactive media strengthens the application of deep learning in the classroom. Literature findings also emphasize that successful implementation is greatly influenced by the teacher's role as facilitator, curriculum readiness, and a collaborative learning environment. Thus, deep learning not only improves the quality of student understanding but also serves as an effective strategy in shaping the profile of Pancasila learners who are critical, creative, and adaptive to the challenges of the 21st century. This article is expected to provide theoretical and practical contributions to elementary school educators in designing more meaningful learning strategies